Consumption, wealth and business cycles: why is Germany different? - Britta Hamburg; Mathias Hoffmann; Joachim Keller (Deutsche Bundesbank, 2005)
This paper studies the long-run relationship between consumption, asset wealth and income - the consumption-wealth ratio - in Germany, based on data from 1980 to 2003. Earlier papers for the Anglo-Saxon economies have documented that departures of these three variables from their common trend signal future changes in asset prices. We find that for Germany they predict changes in income - the consumption wealth ratio predicts business cycles, not stock market cycles. Asset price changes are found to have virtually no effect on German consumption, both in the short as well as in the long-run. Conversely, German asset prices are predictable from the U.S. consumption-wealth ratio. We offer an explanation of these findings that emphasizes structural differences between the bank-based German financial system and the rather market-based Anglo-American system: stock ownership by private households is much less widespread in Germany than in the Anglo-Saxon economies and the share of publicly traded equity in household wealth is much smaller in Germany than in the U.S., the UK or Australia.
Keywords: E44; E32; G20; E21; G12; 330; Wealth Effect on Consumption; Business Cycles; Monetary Policy Transmission; Financial Systems; Asset Price Predictability; Gesamtwirtschaftlicher Konsum; Vermögenszuwachs; Einkommenshypothese; Konjunktur; Bankensystem; Schätzung; Deutschland